Delivery of Alkaline Phosphatase Promotes Periodontal Regeneration in Mice. (August 2021) - Nagasaki, A.; Nagasaki, K.; Kear, B.D.; Tadesse, W.D.; Thumbigere-Math, V.; Millán, J.L.; Foster, B.L.; Somerman, M.J.
Factors regulating the ratio of pyrophosphate (PPi ) to phosphate (Pi ) modulate biomineralization. Tissue-nonspecific alkaline phosphatase (TNAP) is a key promineralization enzyme that hydrolyzes the potent mineralization inhibitor PPi . The goal of this study was to determine whether TNAP could promote periodontal regeneration in bone sialoprotein knockout mice ( Ibsp −/− mice), which are known to have a periodontal disease phenotype. Delivery of TNAP was accomplished either systemically (through a lentiviral construct expressing a mineral-targeted TNAP-D10 protein) or locally (through addition of recombinant human TNAP to a fenestration defect model). Systemic TNAP-D10 delivered by intramuscular injection at 5 d postnatal (dpn) increased circulating alkaline phosphatase (ALP) levels in Ibsp −/− mice by 5-fold at 30 dpn, with levels returning to normal by 60 dpn when tissues were evaluated by micro–computed tomography and histology. Local delivery of recombinant human TNAP to fenestration defects in 5-wk-old wild type (WT) and Ibsp −/− mice did not alter long-term circulating ALP levels, and tissues were evaluated by micro–computed tomography and histology at postoperative day 45. Systemic and local delivery of TNAP significantly increased alveolar bone volume (20% and 37%, respectively) and cementum thickness (3- and 42-fold) in Ibsp −/− mice, with evidence for periodontal ligament attachment and bone/cementum marker localization. Local delivery significantly increased regenerated cementum and bone in WT mice. Addition of 100-μg/mL bovine intestinal ALP to culture media to increase ALP in vitro increased media Pi concentration, mineralization, and Spp1 and Dmp1 marker gene expression in WT and Ibsp −/− OCCM.30 cementoblasts. Use of phosphonoformic acid, a nonspecific inhibitor of sodium Pi cotransport, indicated that effects of bovine intestinal ALP on mineralization and marker gene expression were in part through Pi transport. These findings show for the first time through multiple in vivo and in vitro approaches that pharmacologic modulation of Pi /PPi metabolism can overcome periodontal breakdown and accomplish regeneration.